2018
DOI: 10.1111/1440-1630.12548
|View full text |Cite
|
Sign up to set email alerts
|

Subjective memory complaints and difficulty performing activities of daily living among older women in Australia

Abstract: Background/aim Increased age and cognitive decline have been linked to difficulties with activities of daily living (ADL) and instrumental activities of daily living (IADL). Cognitive decline can often be signalled by complaints about one's cognition, such as memory. With older Australians living longer, there is an increasing proportion of the population at risk of declined performance in daily tasks. The aim of this study was to identify if subjective memory complaints in later life among older women predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…However, we hypothesized that a person's emotional functioning and sense of hope may affect their participation in life and sense of wellbeing. Confirming prior research findings, older adults who were classified as independent in ADL participated more in activities at home and in the community and were more satisfied with their lives (Cordier et al, 2018;Wilson et al, 2013). They expressed higher sense of hope and their emotional status was more positive than older adults classified as dependent in ADL.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, we hypothesized that a person's emotional functioning and sense of hope may affect their participation in life and sense of wellbeing. Confirming prior research findings, older adults who were classified as independent in ADL participated more in activities at home and in the community and were more satisfied with their lives (Cordier et al, 2018;Wilson et al, 2013). They expressed higher sense of hope and their emotional status was more positive than older adults classified as dependent in ADL.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in life expectancy presents challenges in understanding how to best promote healthy aging and create health systems and economic policies to support the growing aging population (Bloom et al, 2015;Whitley et al, 2016). Current research is beginning to recognize that maintaining engagement in meaningful occupations, wellbeing and independence may be a stronger factor in healthy aging than health status alone (e.g., Chippendale & Boltz, 2015 ;Cordier et al, 2018;George & Gough, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study examining the relationship between SMCs and well-being in older community-dwelling adults reported that SMCs were associated with low well-being, daytime sleepiness, and low IADL performance [9]. Several studies have suggested a relationship between the female gender and SMCs and IADLs [10,11]. It is conceivable that complex IADL independence is likely to decline once a person begins to experience SMCs.…”
Section: Introductionmentioning
confidence: 99%